SEKE DAN IKAN MALALUGIS di Desa Bebalang, Kabupaten Kepulauan Sangihe, Sulawesi Utara - Ratmaya, Widya (Sabda: Jurnal Kajian Kebudayaan, 2013)
Coastal society is a group of indigenous people or local people who reside or live in coastal regions and have particular custom in managing its surroundings/row generation to generation. The people manage their coastal resource traditionally and locally; their social structure and activities are still simple. The people have their local wisdom, namely Hak Ulayat Laut, which can conceptually be translated into sea tenure. Hak Ulayat Laut is a form of communal marine resource management. The traditional local wisdom can be manifested in social values, custom norms, ethics, system of belief, traditional site planning, as well as tools and environment-friendly simple technology. The fishing community of Bebalang Village, Sangihe Islands Regency, is a group of indigenous people who have their local wisdom in maintaining and using marine resource. The local wisdom is manifested in a traditional institution which manages the usage of the available natural resources. In the institution there are a number of rules concerning the usage of marine resource as well as the applicable technology and territorial-operating borders. Besides that, the people of Bebalang Village uphold the law regulating the catching of malalugis, a species of kite fish. They catch malalugis by using seke, bamboo-woven traps. The traps appear like bubu, but they have bigger sizes.